Pengaruh kecepatan udara dan massa gabah terhadap kecepatan pengeringan gabah menggunakan pengering terfluidisasi - Syahrul, S.; Mirmanto, M.; Romdani, S.; Sukmawaty, S. (Universitas Mataram, 2017)
Grain processing does not meet the actual grain harvests. This is due to the unsuitable drying process. Milling grain entrepreneurs and farmers in Indonesia are currently conducting a drying process under the sun. Based on the National Standards Body (BSN), grain moisture content must be at 14% to maintain the grain at high qualities. The purpose of this study is to determine the effect of velocity and grain mass variations on drying times. The grain used in this study contains an initial moisture content of 22% ± 0.5%. The grain is dried by inserting it into the drying chamber and varying the air velocities and grain mass. The air velocities used are 4 m/s, 5 m/s, 6 m/s and the variations of the grain mass are 1 kg 2 kg and 3 kg. The results show that increasing the air velocity decreases the drying time. On the other hand, when the grain mass is increased, the drying time elevates. The air velocity and mass of the grain that results in the fastest drying time are 6 m/s and 2 kg. The time required for achieving the water content of 13.6% is 30 menit. At the air velocity of 4 m/s, and the grain masses of 1 kg, 2 kg, and 3 kg, to achieve moisture contents of 13.4%, 13.5% and 13.4% the drying time needs 50 minutes.